DER DAN CR TERHADAP ROA PADA PERBANKAN DI BEI PERIODE 2020-2022 - Nazwa, Karmina (Fakultas Ekonomi Prodi Akuntansi, 2024)
This research aims to determine and analyze the influence of the Debt To Equity Ratio and Current Ratio on the Financial Performance of Banking Companies on the IDX for the 2020-2022 period. In carrying out its business activities, banks need to provide sufficient capital to enable them to operate economically and not experience financial difficulties. Thus debt is an element of the company's capital structure. Capital structure theory explains that a company's financial policy in determining its capital structure aims to optimize company performance. The sampling method was purposive sampling, with a sample size of 96. The data analysis technique was multiple linear regression analysis. The results of this research partially show that DER has no effect on financial performance, while CR has a significant positive effect on financial performance and simultaneously DER and CR have a significant positive effect on financial performance in banking companies listed on the IDX for the 2020-2022 period.